2011
DOI: 10.3928/01477447-20110714-37
|View full text |Cite
|
Sign up to set email alerts
|

Distal Femoral Varus Osteotomy: Unloading the Lateral Compartment: Long-term Follow-up of 45 Medial Closing Wedge Osteotomies

Abstract: Distal femoral medial closing wedge osteotomy is useful for mechanical axis realignment to unload the lateral compartment of the valgus knee. The primary indication for unloading the lateral compartment is lateral unicompartmental osteoarthritis. Alternative treatment options include lateral unicompartment or total knee arthroplasty (TKA). Prerequisites for the osteotomy include a 90° arc of motion, age younger than 60 years, and an active patient capable of an extensive period of rehabilitation. Surgery is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 8 publications
4
55
0
4
Order By: Relevance
“…Sternheim et al [17] recently reported on the outcome of 45 knees treated with medial closing-wedge distal femoral osteotomy for lateral compartment arthritis. Survivorship at 10, 15, and 20 years was 90%, 79%, and 21.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sternheim et al [17] recently reported on the outcome of 45 knees treated with medial closing-wedge distal femoral osteotomy for lateral compartment arthritis. Survivorship at 10, 15, and 20 years was 90%, 79%, and 21.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Good results are reported for closing wedge DFOs at 10 years of follow up with survival rates ranging between 64% (42) and 89.9% (43 (9) reported survival rate of 52.5% at the same follow-up. A recent review confirm the significantly increasing of failure rates in follow-up longer than 10 years (7).…”
Section: Resultsmentioning
confidence: 96%
“…Several authors have since reproduced excellent results using the technique of Healy et al in appropriately selected patients with unicompartmental disease. 11,13,17,18 With its proven track record, the indications for this procedure have been expanding in recent years. Several authors have advocated performing a DFO in the setting of valgus deformity with associated MCL incompetence 5,6 ; however, there remains a paucity of literature regarding this topic.…”
Section: Varus-producing Osteotomymentioning
confidence: 99%
“…[2][3][4] Recently, the indications for varus-producing DFOs have expanded to include the treatment of valgus malalignment in the setting of central or medial ligamentous instability or incompetence. [5][6][7][8][9][10][11][12][13][14] This is of particular importance and utility because several authors have also reported that healing of both the native and reconstructed medial collateral ligament (MCL) is impaired with persistent valgus deformity at the knee. 6 For this reason, many surgeons now choose to perform a DFO to correct the valgus deformity at the knee not only in the setting of isolated lateral compartment pathology but also in the setting of medial ligamentous incompetence.…”
mentioning
confidence: 99%